2006
DOI: 10.1002/iroh.200510835
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Diet of 0+ Fish within a Canyon-Shaped European Reservoir in Late Summer

Abstract: The distribution and diet of age 0+ fish were studied in the deep canyon-shaped Římov Reservoir (Czech Republic), which is characterized by a longitudinal trophic gradient. During late summer of two years, 0+ fish were sampled from inshore and offshore habitats along the longitudinal reservoir axis. Offshore catches of 0+ fish from the surface layer were dominated by roach (Rutilus rutilus), bream (Abramis brama) and perch (Perca fluviatilis), whereas in the deeper open water perch predominated. Inshore catche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 37 publications
7
56
4
Order By: Relevance
“…Similar differences in feeding preference for planktonic crustaceans were confirmed by other field studies comparing the diets of juvenile perch and roach (Hammer 1985;Jachner 1991;Matěna 1995Matěna , 1998Macháček & Matěna 1997). Most recently Vašek et al (2006) evaluated the diet of 0+ perch and roach in offshore and inshore habitats of Římov Reservoir and similarly to our results found that copepods were an important prey of perch in both habitats, with a change from cyclopoid to calanoid copepods along the longitudinal profile of the reservoir as calanoid copepods replaced the cyclopoid towards the dam area.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar differences in feeding preference for planktonic crustaceans were confirmed by other field studies comparing the diets of juvenile perch and roach (Hammer 1985;Jachner 1991;Matěna 1995Matěna , 1998Macháček & Matěna 1997). Most recently Vašek et al (2006) evaluated the diet of 0+ perch and roach in offshore and inshore habitats of Římov Reservoir and similarly to our results found that copepods were an important prey of perch in both habitats, with a change from cyclopoid to calanoid copepods along the longitudinal profile of the reservoir as calanoid copepods replaced the cyclopoid towards the dam area.…”
Section: Discussionsupporting
confidence: 85%
“…As a consequence, young-of-the-year perch and roach dominate the 0+ fish communities of these aquatic ecosystems. A general succession from the dominance of perch to roach with increasing ecosystem productivity has been documented for lakes of different trophic status (Persson et al 1991;Jeppesen et al 2000;Olin et al 2002), and when comparing fish community structure within reservoirs Effect of prey movement apparency and evasiveness on 0+ fish foraging success 787 with pronounced longitudinal gradients (Vašek et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, copepods comprise one half of the perch diet in the Ř ı´mov reservoir in spring (Peterka and Mateˇna, 2009). It has been suggested that a lack of extensive littoral habitats along with the occurrence of regular oxygen deficiency in deeper strata limits the area of fish feeding to the epilimnion where an abundant zooplankton community is available (Kubecˇka et al, 1998;Vasˇek et al, 2006). Our experimental fish stock was higher in comparison with the current estimation of the reservoir fish biomass but did not exceed biomass in the past years.…”
Section: Discussionmentioning
confidence: 99%
“…Kitchell and Kitchell, 1980;Nykänen et al, 2006;Manca et al, 2007). The ecological role of fish in lake ecosystems is invaluable, because they affect the abundance and diversity of their prey organisms, such as planktonic and benthic Cladocera and Diptera larvae (Kornijóv et al, 2005;Vašek et al, 2006;Davidson et al, 2007) through topdown control (Vanni et al, 1997). Fish are also significant due to their participation in internal loading and recycling of nutrients that may affect planktonic organisms (Horppila et al, 1998).…”
Section: Introductionmentioning
confidence: 99%